Key role of elastic vortices in the initiation of intersonic shear cracks; Physical Review E; Vol. 91, iss. 6 - Psakhie S. G. Sergey Grigorievich; Shilko E. V. Evgeny Viktorovich; Popov M. Mikhail; Popov V. L. Valentin Leonidovich (2015, 2015)
Title screen